2015
DOI: 10.1158/0008-5472.can-14-3394
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis Suppressors Regulate the Tumor Microenvironment by Blocking Recruitment of Prometastatic Tumor-Associated Macrophages

Abstract: Triple-negative breast cancer (TNBC) patients have the highest risk of recurrence and metastasis. Because they cannot be treated with targeted therapies, and many do not respond to chemotherapy, they represent a clinically underserved group. TNBC is characterized by reduced expression of metastasis suppressors such as Raf Kinase Inhibitory Protein (RKIP), which inhibits tumor invasiveness. Mechanisms by which metastasis suppressors alter tumor cells are well characterized; however, their ability to regulate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 35 publications
(48 reference statements)
1
102
0
Order By: Relevance
“…It is well-known that chemokines are involved in recruitments of monocytes/macrophages in cancer (40,41). Indeed, chemokine ligand 5 (CCL5) production was increased in HCC cells treated with rSPON2 comparing with controls ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 95%
“…It is well-known that chemokines are involved in recruitments of monocytes/macrophages in cancer (40,41). Indeed, chemokine ligand 5 (CCL5) production was increased in HCC cells treated with rSPON2 comparing with controls ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 95%
“…These cytokines are primarily linked to monocyte recruitment and are known to be able to elevate TAM levels in tumors (Soria and Ben‐Baruch, 2008). Their role in modulating macrophage phenotype/functions is less clarified, although it has been demonstrated that CCL5 can promote prometastatic phenotype of TAMs (Frankenberger et al ., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…CCL5 is produced by CRC cells and by T cells at the margin of CRCLM (69). CCL5/CCR5 signaling has pleiotropic effects including recruitment of monocytes and M2 polarization, promoting the expansion of cancer-associated fibroblasts and enhancing TGFβ-mediated killing of CD8 + T cells by Treg (69, 70). A recent Phase 1 trial with a CCR5 antagonist demonstrated activity against advanced refractory CRCLM, identifying it as a target worthy of further clinical investigation (69).…”
Section: B Clinical-translational Advancesmentioning
confidence: 99%